Iodine Deficiency Disorder and Goitre among School Children in Sarawak -A Nationwide Study. - Lim, Kuang Kuay; Chan, Ying Ying; Ahmad Ali Zainuddin,; Teh, Chien Huey; Hasimah Ismail,; Lim, Kuang Hock; Kee, Chee Cheong (Universiti Kebangsaan Malaysia, 2013)
Iodine deficiency disorders (IDD), is one of the most important micronutrient deficiencies which has multiple adverse effects on growth and development. The aim of this study was to determine the prevalence of IDD among school children and to elucidate the distribution of iodized salt at household level in Sarawak, East Malaysia.